Comparative of Face to Face Learning vs Online Learning: Analysis of Students' Scientific Article Writing Skills Through Project-Based Learning - Tressyalina Tressyalina; Vivi Indriyani; Herlin Triana (Institut Agama Islam Negeri Imam Bonjol Padang, 2023)
Online and face-to-face learning represent distinct educational contexts. Online learning refers to education or instruction conducted over the internet, whereas face-to-face learning occurs in a shared physical space and time. Nowadays, teachers have various options for conducting these learning processes. Each mode of learning possesses its own strengths and limitations. Consequently, this research aims to compare face-to-face and online learning in terms of students' skills in reproducing scientific article using Project-Based Learning (PjBL). This research method is a quantitative research with a quasi-experimental design. Two classes were selected as samples of this study using purposive sampling techniques. With the provision that one class is experimental class 1 by treating students in face-to-face learning mode using the PjBL model, while experimental class 2 learning is carried out online using the PjBL model. The research instrument used was a performance test, namely students making scientific papers. Analysis of research data using SPSS with the stages of normality test, homogeneity test, and t-test. The results of the study showed that there was a difference in the average learning outcomes of students, namely scientific writing skills using Project Based Learning between face-to-face learning and online learning. The results of this study can be concluded that learning with face-to-face classes obtains better learning outcomes compared to the Project Based Learning model which is better than online classes